Pemenuhan Hak Dan Kewajiban Warga Negara Yang Sesuai Dengan Nilai – Nilai Pancasila - Agnes Tika; Dian Aulia; Tarisya Arliani Munandar (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses the importance of fulfilling the rights and obligations of citizens in accordance with the values of Pancasila. In this context, values such as justice, unity, democracy, prosperity and belief in the one and only God are the main foundation. The emphasis on fulfilling rights includes human rights, participation in democratic life, and legal protection, while obligations include obedience to the law, compliance with social norms, and active contribution to nation building. Through the strong implementation of Pancasila values, it is hoped that a just, prosperous and prosperous society can be realized in accordance with the ideals of the Indonesian nation.